Flow space reveals the urban network structure and development mode of cities in Liaoning, China - Shenzhen Tian; Jialin Jiang; Hang Li; Xueming Li; Jun Yang; Chuanglin Fang (Humanities & Social Sciences Communications, 2023)
Abstract As an important supplement to “location space”, “flow space” has become an important trend in urban network research. At present, the theoretical basis and empirical research of urban network structure from the perspective of “flow space” are not completely clear. Based on the urban spatial network structure research system framework, this paper comprehensively studies the urban spatial structure, spatial network pattern and development mode of Liaoning Province in China by using multivariate data flow. The results show that: (1) Cities at all levels in Liaoning Province have different functions and roles in the urban network level, with Shenyang and Dalian as the leading cities, and Anshan and Jinzhou as “transit hubs”; (2) Liaoning Province takes Shenyang-Dalian as its main axis, the Shenyang economic circle with Shenyang as the core and the coastal economic belt with Dalian as the core and Dandong and Yingkou as the two wings intersect to form the urban spatial network pattern; (3) In the future, Liaoning Province should further form the urban development model of “core city-axis-cluster”. Under the trend of globalization, it should carry out in-depth promotion in combination with “Shenyang Modern Metropolitan Circle” “Liaoning Coastal Economic Belt” and “Liaoning Northwest Strategy”, and finally form a balanced, efficient and comprehensive urban network structure.